Elaboration of a Method for the Determination of Low-Molecular-Weight Mustard Gas Biomarkers in Biological Samples - D. О. Korneev; L. V. Petrakova; М. А. Ponsov; А. А. Rodionov (Вестник войск РХБ защиты, 2023)
The relevance of the development and the improvement of methods for the determination of metabolites (biomarkers) of toxic substances in biological fluids (blood, urine, etc.) is associated with the need to establish facts of humans and animals exposure to toxic chemicals. The need for such analysis arises within the framework of monitoring of the compliance with the provisions of the Chemical Weapons Convention (CWC), when conducting investigations into the alleged use of chemical agents, as well as within the framework of the official proficiency tests carried out by the Organization for the Prohibition of Chemical Weapons (OPCW). Nowadays there exists the problem of the determination of lowmolecularweight mustard gas biomarkers in biological samples with the use of gas chromatography methods with massselective detection. The lowmolecularweight biomarkers of sulfur mustard (SM) are thiodiglycol, oxides and sulfoxides. The identification and quantitative assessment of SM markers in blood and urine is carried out according to the methods, based on the displacement of thiodiglycol and its derivatives from protein conjugates with titanium trichloride, solidphase extraction, concentration in ethyl acetate solution, derivatization with pentafluorobenzoyl chloride, heptafluorobutyrylimidazole, heptafluorobutyric acid anhydride or chloride, subsequent stripping of the derivative into the appropriate solvent and GHMS analysis (chemical ionization technique with methane as a reagent gas with the registration of negative ions). After the sample preparation, the limits of detection of the minimum values of ultralow concentrations of the analyzed biomarkers of SM in urine and blood plasma were determined. After the chromatographic analysis, the corresponding graphs of indicators have been constructed, based on the concentrations of biomarkers in urine and blood plasma. Later on they have been used for the elaboration of the methods for the determination of SM biomarkers in human urine and blood.